1997
DOI: 10.1046/j.1365-2958.1997.5521918.x
|View full text |Cite
|
Sign up to set email alerts
|

Dephosphorylation of the phosphoprotein PII in Synechococcus PCC 7942: identification of an ATP and 2‐oxoglutarate‐regulated phosphatase activity

Abstract: The phosphorylation state of the putative signal transduction protein P(II) from the cyanobacterium Synechococcus sp. strain PCC 7942 depends on the cellular state of nitrogen and carbon assimilation. In this study, dephosphorylation of phosphorylated P(II) protein (P[II]-P) was investigated both in vivo and in vitro. The in vivo studies implied that P(II)-P dephosphorylation is regulated by inhibitory metabolites involved in the glutamine synthetase-glutamate synthase pathway of ammonium assimilation. An in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 34 publications
1
62
0
Order By: Relevance
“…In nitrate-grown cells, the phosphorylation state of PII is intermediate and increases with increasing CO 2 supply, whereas inhibition of CO 2 fixation leads to dephosphorylation of phospho-PII (PII-P). Through in vitro analysis of PII-kinase and phosphatase activities, we suggested that these activities are localized on different polypeptides, and that both PII phosphorylation and dephosphorylation are regulated by the metabolite-binding status of PII with its ligands 2-oxoglutarate and ATP (20). Moreover, we were able to characterize a Mg 2ϩ -dependent PII-P phosphatase activity in partially purified preparations of Synechococcus PCC 7942 extracts (20).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In nitrate-grown cells, the phosphorylation state of PII is intermediate and increases with increasing CO 2 supply, whereas inhibition of CO 2 fixation leads to dephosphorylation of phospho-PII (PII-P). Through in vitro analysis of PII-kinase and phosphatase activities, we suggested that these activities are localized on different polypeptides, and that both PII phosphorylation and dephosphorylation are regulated by the metabolite-binding status of PII with its ligands 2-oxoglutarate and ATP (20). Moreover, we were able to characterize a Mg 2ϩ -dependent PII-P phosphatase activity in partially purified preparations of Synechococcus PCC 7942 extracts (20).…”
mentioning
confidence: 68%
“…In Vitro Assays of PphA Reactivity Toward PII-P. Phosphorylated PII was purified as described (20) with the following modifications: (i) The cells were grown in modified BG11 medium (containing only 1 mM sodium nitrate) to an optical density (OD 750 ) of 0.9, which caused initial nitrogen chlorosis, and thus, a maximal degree of PII phosphorylation (28); (ii) the heparin Econo-Pac cartridge was developed with a 200-ml gradient. The PII protein obtained was highly phosphorylated with almost exclusively the form PII 3 and a small amount of PII 2 .…”
Section: Cloning and Purification Of Overexpressed Ppha Protein (Sll1mentioning
confidence: 99%
“…2-Oxoglutarate synthesis by isocitrate dehydrogenase is the final step of the oxidative branch of the TCA cycle in cyanobacteria (Tandeau de , and its consumption via GOGAT is directly coupled to ammonium assimilation. Consequently, limitation of the GS-GOGAT cycle by ammonium depletion leads to accumulation of 2-oxoglutarate, which serves as an indicator of the cellular nitrogen status (Irmler et al, 1997;Forchhammer, 1999;Muro-Pastor et al, 2001). Two 2-oxoglutarate-responsive elements, P II and NtcA, have been recognized so far in cyanobacteria.…”
Section: Acclimation To Nitrogen Deprivationmentioning
confidence: 99%
“…In the cyanobacteria Synechococcus elongatus, the protein kinase that phosphorylates PII could only be detected during in vitro assays if both ATP and 2-ketoglutarate were present (as effectors) (Forchhammer and Tandeau de Marsac, 1995). A type 2C phosphatase was identified as the PII protein phosphatase, and its ability to dephosphorylate PII is also regulated by ATP and 2-ketoglutarate, but in a reciprocal manner to the PII protein kinase (Irmler et al, 1997). This property of the 2C phosphatase was not observed if nonphysiological substrates (phosphoproteins other than PII) were employed, illustrating that these metabolites maintain PII in a conformation that controls (de)phosphorylation.…”
Section: Pii Signaling: Sensing In Bacteria and The Chloroplastmentioning
confidence: 99%